FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ANGKA KUMAN UDARA DI RUANG RAWAT INAP KELAS III RSUD DR. MOEWARDI SURAKARTA - Didik Agus Nugroho; Budiiyono Budiyono; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2016)
Treatment room is an important part of Hospital institution; in addition to be the place where the healthcare officers do their activity, treatment room is also the place most frequently used for visitor or society and family waiting for the patient so that cross infection or nosochomial infection more likely occurs. The objective of research was to find out the factors related to airborne germ rate in the third class of Melati inpatient room in Surakarta Dr. Moewardi Local General Hospital. The research method employed in this study was observational one with cross-sectional approach. The population of research was the third class of Melati inpatient room. Data analysis was carried out using univariate and bivariate analysis technique with chi-square test. The result of research showed that the mean temperature was 24.40C, mean humidity was 62.7%, mean illumination 113.7 lux, and mean airborne germ rate was 256.5 CFU/m3. The variables related to airborne germ rate were temperature with p-value 0.002, humidity with p-value 0.005, illumination with p-value 0.001, while the variables not related to airborne germ rate were sterilization frequency with p-value 0.075, visitor number with p-value 0.184, rubbish basket condition with p-value 0.169, linen condition with p-value 0.169, and patient’s personal hygiene condition with p-value 0.300. Conclusions of this study are factors related and  have an influence on the growth of germs number of air in the third class of Melati inpatient room in Surakarta Dr. Moewardi Local General Hospital that is temperature, humidity, light intensity.